Adsorption of Methylene Blue on Activated Carbon Surfaces Obtained by Shock Compression of Graphite Using Reactive Molecular Dynamics - Tomasz Panczyk; Pawel Wolski; Krzysztof Nieszporek; Robert Pietrzak (Molecules)
This study explores the formation of functionalized carbon surfaces through shock compression of graphite in the presence of water, modeled using molecular dynamics and the ReaxFF reactive force field. The shock compression method produces activated carbon with surface functionalities, primarily hydroxyl groups, and varying morphological properties. Two approaches, unidirectional and isotropic compression, yield distinct surface structures: the former preserves a relatively flat surface, while the latter generates corrugated features with valleys and ridges. These features significantly impact the adsorption properties of methylene blue (MB), a commonly used dye. Simulations reveal that MB molecules are highly mobile on flat surfaces, aligning with a mobile adsorption model. However, on corrugated surfaces, MB exhibits localized adsorption, with the deepest valleys effectively immobilizing the dye molecules. Additionally, the study highlights the influence of surface hydroxyl groups, which, through interactions with water molecules, prevent MB from occupying these regions. The findings underscore that traditional adsorption models may not fully capture the dynamics of MB adsorption on activated carbons with complex morphologies. These insights are critical for advancing carbon-based adsorbents in water purification applications.